"I May Be a Native Speaker but I'm Not Monolingual": Reimagining All Teachers' Linguistic Identities in TESOL. Issue 3 (September 2016) - Ellis, Elizabeth M.
Abstract : Teacher linguistic identity has so far mainly been researched in terms of whether a teacher identifies (or is identified by others) as a native speaker (NEST) or nonnative speaker (NNEST) (Moussu & Llurda, 2008; Reis, 2011). Native speakers are presumed to be monolingual, and nonnative speakers, although by definition bilingual, tend to be defined by their perceived deficiency in English. Despite widespread acceptance of Cook's (1999) notions of second language (L2) user and multicompetence, and despite major critiques of the concept of the native speaker (Davies, 2003; Hackert, 2012), the dichotomy lives on in the minds of teachers, learners, and directors of language programs worldwide. This article sets out to show that the linguistic identities of TESOL teachers are varied and complex, and that the dichotomy does little justice to this complexity. Findings are reported from the linguistic biographies of 29 teachers of adult TESOL in seven countries, and a detailed account is given of the rich linguistic identities of two of those teachers, one in Japan and one in Canada. The findings bear out those from Ellis (2013) undertaken in the Australian context. The article concludes with a call for recognition of the plurilingual multicompetencies of all TESOL teachers, and for these identities to be valued in the context of the TESOL classroom to assist learners who are becoming plurilingual.